Counselling Guidance Teacher's Efforts in Overcoming the Crisis of Student Character Education - Fatharani, Yuni; S., Irwan (Scaffolding: Jurnal Pendidikan Islam dan Multikulturalisme, 2023)
This research aims to discover that Indonesian children's increasingly strange character events are of particular concern to education observers. This research is qualitative, using a case study approach. The research location is at SMPN 2 Babalan, Langkat, North Sumatra. Research data in the form of guidance and counselling teacher activities in overcoming student character education sourced from teachers, students, and stakeholders. Observation, interviews, and documentation do data collection techniques. While data analysis with data reduction, data presentation, conclusion drawing, and verification showed that counselling guidance teachers could help students understand and internalize positive values by holding discussions, lectures, or other interactive activities. They can also advise students on dealing with social pressure and resolve conflicts in daily life. In addition, counselling teachers act as mediators between students, teachers, and parents. They can assist in conveying problems related to character education to related parties and help find appropriate solutions. Counselling guidance teachers' efforts can be more effective and integrated into the educational environment by involving parents and teachers. Overall, counselling guidance teachers' efforts to overcome the crisis of student character education have an important role in shaping a young generation with good character. With the right support and guidance, students can overcome character education problems and develop into individuals with integrity, responsibility, and positive attitudes in everyday life.